493 SLIDING SCALE COMMUNITY WELLNESS IN RURAL MONTANA. Issue 1 (1st January 2007) - Phillips, C.
Abstract : Purpose: Meagher County, MT, has a population of 2, 000 people, over 500 of whom are uninsured. A sliding fee wellness program was developed to cover the uninsured by using excess capacity in labor and space from the medical center. Methods: The program is based on the 5-year-old Employee Wellness Program in place at Mountainview Medical Center in White Sulphur Springs. Feedback about the employee program was obtained from medical center staff and was used to create a community program with a sliding fee schedule based on federal poverty guidelines. A marketing plan and informational tools were developed to launch the program. Community leaders were recruited to elicit support and improve visibility of the new plan. A focus group of community and hospital board members was held to determine the efficacy of the promotion materials that were developed. Results: Materials were distributed directly to every household in Meagher County, and a "kickoff" event was held to introduce the program as well. Feedback was very positive from the public during the preintroduction phase, and the number of enrollees is growing as word of mouth spreads. Conclusion: Public support was overwhelming, and residents were very excited to have help with the cost of their care. The program is will be overseen by the medical center's CEO and CMO, who will assess the program every 6 months to ensure effectiveness and fiscal feasibility.